EFEKTIVITAS PEMBINAAN DAN PELATIHAN GELANDANGAN DAN PENGEMIS OLEH DINAS SOSIAL DAN PEMAKAMAN KOTA PEKANBARU - Yuki Deli A.M; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The Effectivity of Homeless and Beggars Founding and Training Implemented by the Social and Cemetery Departement of Pekanbaru City. . And the purpose of this research are to know the efectivity of the founding and training of homeless and beggars by the Departement of Social and Cemetery of Pekanbaru and factors concerning the halt of progress of the founding and training. This research using the method of qualitative descriptive and data collection technique by the way of observation, interview, and library research obtained by research informant that has been predetermined based on snowball sampling technique. Based on research result that has been done based on the concept and theory researcher found out that the homeless and beggars founding and training provided by Pekanbaru’s Department of Social and Cemetery is not yet effective. This can be seen by the many homeless and beggars still lurking in PekanbaruKeywords: Effectivity, Founding And Training, Source Approach, Process Approach, Targeted Approach